Synthesis, Characterization, and Biodegradation of Novel Starch Grafted Zincated Nanoclay Polymer Biocomposites. Issue 5 (24th March 2022) - Mandal, Nintu; Datta, S.C.; Manjaiah, K.M.; Dwivedi, B.S.
ABSTRACT: Novel starch grafted zincated nanoclay polymer bio-composites (SZNCPBCs) were synthesized with variable percentages (8%, 10%, and 12%) of clay and nanoclay, acrylic acid, and acrylic amide as monomers, N, N-Methylene bisacrylamide (NNMBA) as crosslinker and ammonium persulfate (APS) as initiator. Clays, as well as SZNCPBCs were characterized viz . X-ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). Nanocomposite containing 12% nanoclay showed the slowest release rate. However, 8% clay containing nanocomposite recorded higher Olsen-P content and equilibrium water absorbency. SZNCPBCs proved to be an innovative controlled release Zn fertilizer formulation. GRAPHICAL ABSTRACT: uf0001